METTL3-Mediated m6A RNA Modification Regulates Corneal Injury Repair. (22nd October 2021) - Dai, Yarong; Cheng, Maosheng; Zhang, Siyan; Ling, Rongsong; Wen, Jieqi; Cheng, Yifan; Huang, Boxuan; Li, Jinrong; Dai, Caifeng; Mao, Shiqing; Lin, Shuibin; Shen, Huangxuan; et al.
Abstract : Limbal stem cells are essential for continuous corneal regeneration and injury repair. METTL3-catalyzed N6-methyladenosine (m 6 A) mRNA modifications are involved in many biological processes and play a specific role in stem cell regeneration, while the role of m 6 A modifications in corneal injury repair remains unknown. In this study, we generated a limbal stem cell-specific METTL3 knockout mouse model and studied the role of m 6 A in repairing corneal injury caused by alkali burn. The results showed that METTL3 knockout in the limbal stem cells promotes the in vivo cell proliferation and migration, leading to the fast repair of corneal injury. In addition, m 6 A modification profiling identified stem cell regulatory factors AHNAK and DDIT4 as m 6 A targets. Our study reveals the essential functions of m 6 A RNA modification in regulating injury repair and provides novel insights for clinical therapy of corneal diseases.